“Beat the Copper Nail in the Eye with a Hammer”: An Ancient Magic Spell in Yiddish for Catching a Thief - Zaidman-Mauer, Daniella (European journal of jewish studies, 2023)
Exposing a thief magically with the aid of a painted eye on the wall, has existed since antiquity. The spell includes instructions for drawing an eye, incantations, summoning up God’s help, and knocking a nail into the painted eye, thus harming the thief’s eye and exposing him. In this article we present the same spell written in Yiddish dating between the fifteenth to the sixteenth century. In tracing the Yiddish spell’s sources for both the text and its illustration, our examination reinforces previous scholarship of magical praxis, which asserts that rituals are cross-cultural and cannot always be traced to its Jewish or non-Jewish origins.